Socioenvironmental change as a process: Changing foodways as adaptation to climate change in South Greece from the Late Bronze Age to the Early Iron Age. (30th September 2021) - Dibble, Flint; Finné, Martin
Abstract: Recent interest in modern climate change has stimulated extensive scientific study into past societal responses to climate variability. However, examining climate change and society as a historical narrative drawing upon politics, economics, and settlement patterns does not provide a direct link between climate and society. Given that most inhabitants of the premodern world engaged in agriculture and/or pastoralism, examining chronological correlations between climate and foodways, not as a historical narrative but as a longterm socioenvironmental process, has the potential to identify direct societal adaptations to a changing environment. From South Greece there is evidence for drier conditions at the end of the Late Bronze Age. Is the disappearance of writing, art, and many known settlements at the end of the Bronze Age an example of collapse in the face of inability to adapt to climate change? This is a difficult question to answer given the coarse resolution of many of our archaeological and climatic datasets. Settlement faunal records suggest that food production systems became increasingly homogenous in Late Bronze Age Greece, potentially due to an elite control over various production systems that promoted intensification of certain products. However, in the first millennium B.C.E., animal husbandry, specifically, and food production systems, more broadly, became more heterogenous, and a proportional increase in goats in areas with less rainfall was likely an adaptive response to the drier climate. This paper examines the adaptive relationship between foodways and climate and argues for a process driven approach when explaining social responses to ancient climate change.